A evolução da indústria petroquímica brasileira The evolution of the brazilian petrochemical industry - Eduardo Mc Mannis Torres (Química Nova, 1997)
The Brazilian Petrochemical Industry is about to turn fifty years old, and endures profound changes. In less than four years, it has moved from a system of centralized decisions and a national lever of planning, to another which is spread, without massive actions and with less integration with the raw material supplying company. On this issue it is presented, briefly, a small history of the development of this industrial type, including issues on how the growth of this activity, so important to the development of Brazil, shall be lead.